Retrospective evaluation of the pre- and postoperative factors influencing the sensitivity of localization studies in primary hyperparathyroidism. (January 2016) - Medas, Fabio; Erdas, Enrico; Longheu, Alessandro; Gordini, Luca; Pisano, Giuseppe; Nicolosi, Angelo; Calò, Pietro Giorgio
Abstract: Introduction: Over the last decades, mini-invasive surgery has become increasingly common for treatment of primary hyperparathyroidism; such approach requires preoperative localization of a suspected parathyroid adenoma. Neck ultrasound (US) and technetium-99 m sestamibi (MIBI) scan are the main imaging studies used for this purpose. The aim of the present study is to evaluate what pre- and post-operative factors may alter the reliability of localization studies. Methods: A retrospective analysis on 212 patients with preoperative diagnosis of primary hyperparathyroidism was conducted. Data collected included demographic data, preoperative workup, operative findings and follow-up. Univariate logistic regression was performed on pre- and postoperative variables. Results: US sensitivity was 62.4% and MIBI sensitivity 78.9%. Cure rate after parathyroidectomy was 98.1%. Univariate logistic regression demonstrated that US sensitivity was impaired by lower levels of serum calcium (p < 0.0001), multi-gland disease (p = 0.011) and co-existence of thyroid disease (p = 0.001); MIBI sensitivity was impaired by lower levels of serum calcium (p = 0.001) and multi-gland disease (p < 0, 0001). Conclusions: Mild hypercalcaemia, multi-gland disease and co-existing thyroid disease are the main factors affecting sensitivity of preoperative imaging studies. In such patients a mini-invasive approach is possible but the use of intraoperative PTH monitoring is mandatory to reduce the risk of unsuccessful surgery. Highlights: Preoperative localization of a suspected adenoma is essential to perform mini invasive surgery in primary hyperparathyroidism. The main factors predicting a low reliability of preoperative localization studies are concomitant thyroid disease and discordant studies. In such cases a mini invasive approach is possible but intraoperative PTH monitoring is mandatory.